Cultural transmission and religious belief: An extended replication of Gervais and Najle (2015) using data from the International Social Survey Programme. - Tatsunori Ishii; Katsumi Watanabe (PLoS ONE, 2024)
Beliefs in supernatural agents or religious beliefs are pervasive, yet there are individual differences in such beliefs. Although various factors have been proposed as relevant, recent research has increasingly emphasized the importance of cultural learning, showing that enthusiastic religious behavior (credibility enhancing displays; CREDs) from parents predicts increased religious beliefs among their children. In addition to this kin-biased learning, Gervais and Najle (2015) analyzed data from the World Values Survey to demonstrate that the number of adults who show religious CREDs is also an important predictor of people's beliefs, indicating that individuals develop their religious beliefs through conformist learning. This pre-registration study aimed to replicate and extend these findings by analyzing data from the International Social Survey Programme (ISSP), which is another large social survey. We examined the generalizability of the results by analyzing multigenerational samples. Multilevel regression and signal detection analyses revealed that the presence of both kin-biased and conformist learning cues was significantly associated with respondents' religious beliefs. Moreover, they suggested tension between the two cultural learning cues, thereby suggesting that the effect of kin-biased learning on religious beliefs becomes stronger (weaker) when the cue for conformist learning is unclear (clear). These results support the idea that these two types of cultural learning are crucial to the development of religious beliefs.